GAYA HIDUP HEDONISME DI KALANGAN MAHASISWA UNIVERSITAS SAM RATULANGI - Vionnalita Jennyya; Maria Heny Pratiknjo; Selvie Rumampuk (HOLISTIK, Journal of Social and Culture, 2021)
Along with the development of the times, the development of technology resulted in changes in values and lifestyles for the community, especially for students. This lifestyle of hedonism has a great appeal to student life. Hedonism has the meaning of a life view that considers that pleasure and material pleasure are the main purposes of life. Students are the next generation of the nation who seek identity through the surrounding environment. Students are very enthusiastic about-new things that are considered interesting. This lifestyle of hedonism has a great appeal to student life. Therefore, it is surprising that intellectual students must have such traits just to satisfy themselves. This is where we can see how the influence of the hedonistic lifestyle for students, because students have a great responsibility as a future leader. This study uses qualitative method, research that uses natural background with the intention of interpreting the phenomenon that occurs. The author uses a naturalistic approach to understand the phenomenon of hedonism.The rise of hedonism among Sam Ratulangi University students is caused by two factors, internal and external. An internal factor is the view of life that says that life is only once and driven by human nature filled with curiosity causes an individual to behave to satisfy his sense of pleasure and satisfaction. Further external factors of friendship groups and from families.Keywords: behavior, student, hedonism